A matching decomposition of the rural-urban difference in malnutrition in Malawi - Richard Mussa (Health Economics Review, 2014)
Background: Child malnutrition remains widespread in many developing countries. Malnutrition during infancy may substantially increase vulnerability to infection and disease, and the risk of premature death. Malnutrition in children may also lead to permanent effects and to their having diminished health capital later in life as adults. These negative consequences of child malnutrition entail that the reduction of child malnutrition is vital for the social-economic development of countries. Urban children generally have better nutritional status than rural children. Malawi is no exception in this regard. The objective of this paper is to explore how much of the rural-urban nutrition gap in Malawi is explained and how much is unexplained by differences in characteristics. Method: Using data from the 2006 multiple indicator cluster survey (MICS), the paper used the Nopo decomposition method to decompose the rural-urban malnutrition gap. This nonparametric method takes into account the fact that the supports of the distributions of characteristics between the two areas can be different. Results: The results show that 90% and 89% of the stunting and underweight gaps respectively would be eliminated if there were no urban children with combinations of characteristics which positively influence child nutrition that remain entirely unmatched by rural children. Further to that, 4% and 6% of the stunting and underweight gaps respectively would disappear if there were no rural children with combinations of characteristics which negatively affect child nutrition that remain entirely unmatched by urban children. Conclusions: These findings suggest that the characteristics which negatively affect child nutrition in rural areas play a small role in the gap, and that most of the gap is largely due to the favourable characteristics such as better parental education and better household economic status among others that urban children have. The findings imply that in order to reduce the malnutrition gap policy interventions should focus more on ensuring that the favourable characteristics that urban children have such as better parental education, better household economic status among others are also available to rural children.
Keywords: 330; Matching; Decomposition; Malnutrition; Malawi